Inklusivitas Jalur Pedestrian di Sekitar Kampus Universitas Muhammadiyah Surakarta, Studi Kasus Penggal Jln. A.Yani, Jln. Garuda Mas dan Jln. Menco Raya Kartasura, Jawa Tengah - Wardani, Dwi Ely; Roychansyah, M. Sani (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 5 No 1 (2018): April 2018, 2018)
The University Campus is a main provider of higher education services for the community. It has an impact on the growth of the surrounding area, and its influence is marked by changes in land use due to the concentration of proximal business and community activities. With the growing density of the residential population, activities around UMS campus area have also resulted in a higher level of community mobility. Therefore, it is necessary to design inclusive pedestrian pathways so that communities in this area may easily move about without having to depend on motor vehicles. In addition, an effort is being made to create a pedestrian-friendly environment for disabled persons in accordance with government policy. Using a qualitative deductive method and through the application of several theories dealing with pedestrian planning, the governing principle of inclusiveness is considered to be compatible with a heterogenic campus. Linda Nussbaumer in her book Inclusive Design A Universal Need, (2012 ) states that the concept of inclusivity consists of six variables, but after due consideration, only 3 variables are used in this study, namely: affordability, convenience, and security. These three variables are then elaborated and used as parameters to measure the level of inclusiveness of pedestrian pathways that accommodate the need of disabled people. Keywords: pedestrian pathway, inclusive, accessibility, convenience, safety